Representation Of Chinese And African Relationship Through Wolf Warrior 2 Film - Cherli Septiani; Rahadjeng Pulungsari Hadi; Adrianus Laurens Gerung Waworuntu (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2022)
Film Wolf Warrior 2 (war Wolf2/ zhàn láng 2) by Wu Jing which was released in 2017, tells the story of a former Special Forces of the People's Liberation Army (TPR) named Leng Feng in Africa. Leng Feng was an employee of the export trade from China to Africa, but with the wars and epidemics that occurred in Africa, Leng Feng had to evacuate Chinese citizens who were in Africa to return to China. The film not only features the main character Leng Feng, but also features a setting in Africa and several dialogues mention things about Africa. Based on the observations made, the writer intends to research the film Wolf Warrior 2 which was released in 2017 which was made and directed by Wu Jing. Observations were made to see how the film Wolf Warrior 2 represents the relationship between China and Africa, and to see its meaning through the scenes in the film. Through descriptive qualitative methods, the researcher found that the film Wolf Warrior 2 displays diplomatic relations between China and Africa.